2007
DOI: 10.1111/j.1472-765x.2007.02202.x
|View full text |Cite
|
Sign up to set email alerts
|

Using skimmed milk agar to functionally screen a gut metagenomic library for proteases may lead to false positives

Abstract: Aims:  Functional screens using skimmed‐milk agar to obtain protease activity is a common approach. The aim of this study was to determine the efficacy of this screen to obtain protease activity from a metagenomic library. Methods and Results:  A distal gut metagenomic library was functionally screened using a skimmed‐milk agar. The functional screen provided 231 clones generating the characteristic clear halo indicative of protease production. Clone analysis revealed that they were not protease‐positive, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 3 publications
0
41
0
2
Order By: Relevance
“…Para a determinação da atividade proteolítica extracelular qualitativa, as bactérias foram semeadas em meio sólido composto por 1% (v/v) de leite desnatado e 1,5% de ágar, como descrito por Jones et al, 13 sendo as temperaturas de incubação modificadas, 30ºC ou 37ºC de acordo com a temperatura de isolamento de cada bactéria, sendo observada em intervalos de 24h durante três dias. A atividade proteolítica foi indicada como uma zona clara ao redor das colônias.…”
Section: D) Atividade Proteolítica Das Bactérias áCido Láticas Isoladunclassified
“…Para a determinação da atividade proteolítica extracelular qualitativa, as bactérias foram semeadas em meio sólido composto por 1% (v/v) de leite desnatado e 1,5% de ágar, como descrito por Jones et al, 13 sendo as temperaturas de incubação modificadas, 30ºC ou 37ºC de acordo com a temperatura de isolamento de cada bactéria, sendo observada em intervalos de 24h durante três dias. A atividade proteolítica foi indicada como uma zona clara ao redor das colônias.…”
Section: D) Atividade Proteolítica Das Bactérias áCido Láticas Isoladunclassified
“…In addition, a serine protease has been mentioned in reviews, but the original work was not published (13,29). In other cases, screening of metagenomic libraries for proteolytic activity was unsuccessful (19,44). Jones et al (19) found glycoside hydrolases instead of proteases during activitybased screening of the human gut microbiome on skim milkcontaining LB medium.…”
Section: Vol 75 2009 Metagenome-derived Metalloproteases 2513mentioning
confidence: 99%
“…In other cases, screening of metagenomic libraries for proteolytic activity was unsuccessful (19,44). Jones et al (19) found glycoside hydrolases instead of proteases during activitybased screening of the human gut microbiome on skim milkcontaining LB medium. These authors concluded that this screen is not entirely suitable for detection of proteolytic enzymes.…”
Section: Vol 75 2009 Metagenome-derived Metalloproteases 2513mentioning
confidence: 99%
See 2 more Smart Citations